APPRECIATION: AN EMPIRICAL REVIEW ON THE COLOSSAL IMPACT ON TELECOM INDUSTRY EMPLOYEE RETENTION IN MALAYSIA - Shonubi, Olurotimi; Abdullah, Norida; Hashim, Rahman; Hamid, Norhidayu (PEOPLE: International Journal of Social Sciences, 2017)
The purpose of this study is to examine the colossal impact of appreciation on employees’ retentionin a telecom industry in Malaysia. A structured Likert questionnaire ranging from strongly agree to strongly disagree will be used for purposes of data collection; while Structural Equation Modeling (SEM-Amos) will be used for the data analysis. Moreover, the respondents will be, employees of Telekom Malaysia in Melaka. Subsequently, this present study having explore various literature that are significant to employee’s intrinsic reward and retention aim to provide updated literatures most especially for researchers in the field of industrial psychology and management generally. This studyalso aim to provide more literature on appreciation as an endogenous and intrinsic motivational factor that can be used in the organization to motivate employees.